Non-Darcy Flow in Hydraulic Flushing Hole Enlargement-Enhanced Gas Drainage: Does It Really Matter? - Qingquan Liu; Yuanping Cheng; Jun Dong; Zhengdong Liu; Kaizhong Zhang; Liang Wang (Geofluids)
In recent years, the non-Darcy flow has seen a significant increase in interest in conventional and unconventional gas developments. The nonlinear behavior can be described by adding a quadratic term of the velocity with the permeability-dependent β factor in Darcy’s law. The methods for improving permeability such as the hydraulic flushing hole enlargement (HFHE) technique can remarkably enhance the coal permeability thus changing the β factor. However, few studies have been done previously to seek how this non-Darcy flow impacts the permeability-enhanced gas drainage. In this study, a fully coupled coal deformation and damage, the non-Darcy flow of free methane gas in the fractures, and Fickian diffusion of adsorbed methane in the coal matrix model were developed. The Klinkenberg effect has been taken into account as a reference object. A series of simulation scenarios were carried out to evaluate and compare the influences of the non-Darcy effect, gas-coal interaction effect, and Klinkenberg effect on the HFHE-enhanced gas drainage. Results of the simulation illustrate that the HFHE technique can significantly improve the gas drainage efficiency by permeability enhancement. But the HFHE-enhanced gas drainage is unique to the other gas developments with high or low flow rates; a slight pressure gradient and short drainage time make the non-Darcy effect fail to generate cumulative influence on the HFHE-enhanced gas drainage.